Ordering of components of Green Supply Chain Practices jointly impacting the individual components of Green Supply Chain Performance – An Empirical Study of the Indian Automobile Manufacturing Sector - Gandhi, Mohd. Asif (Archives of Business Research, 2018)
This paper establishes the order in which five identified green supply chain practices jointly impact ten identified individual component measures of green supply chain performance with reference to the automobile manufacturing sector of India. This research paper is an extension of the research work done by [1]. The purpose of this research paper is to test the hypotheses developed by [1]. Further the joint impact of Green Supply Chain Practices on individual components of Green Supply Chain Performance has been established by means of ten multiple regression models. Consistently the ten multiple regression models that were developed established that there is a definite ordering of the five Green Supply Chain Practices while jointly impacting each of the ten component measures of Green Supply Chain Performance individually. These findings would enable practicing managers in the automobile manufacturing sector of India to take decisions related to implementation of green supply chain practices which would result in enhancing a particular green supply chain performance measure. This information regarding implementation of Green Supply Chain Practices would be very handy as it has financial and policy making implications.